The Atopic Dermatitis Control Tool: A High-Performance Tool for Optimal Support - Delphine Staumont-Sallé; Charles Taieb; Stephanie Merhand; Jason Shourick (Acta Dermato-Venereologica, 2021)
The evaluation of global atopic dermatitis control is key to minimizing disease burden. The Atopic Dermatitis Control Tool (ADCT) has been developed for this purpose. Participants (diagnosed by a physician) were recruited to this observational cross-sectional study using real-life methodology and completed a questionnaire on sociodemographic and personal information. The ADCT algorithm, described by Pariser, was used to categorize patients as having controlled or uncontrolled atopic dermatitis. Data were collected for 1,606 patients. Median age of the patients was 40 years , and 1,023 (63.7%) patients were women. A total of 1,146 (71.4%) patients had uncontrolled atopic dermatitis according to the ADCT score. Patients with uncontrolled disease were at significantly higher risk of a high stress level and were more likely to be absent from work than those with controlled disease. In conclusion, a key factor for predicting disease burden in atopic dermatitis is patient self-assessed disease control in terms of multiple dimensions: stress, sleep, quality of life, work absenteeism and loss of productivity.